Improving Students’ Reading Skill By Using Quantum Learning - Martika, Wini; Hermayawati, Hermayawati (LPPM Universitas Mercu Buana Yogyakarta, 2016)
AbstractThere were many students who had problem in comprehending the text. Based on the problem, this research aimed at finding out :(1) the procedures to improve students’ reading skill using Quantum Learning (QL); (2) the students’ interest in their learning reading using QL; (3) the students’ improvement in comprehending the texts using QL. This research involved 32 students of class VII C of SMPN 1 Seyegan. The researcher used pre-test and post- test to analyse the students’ improvement. It was found that the students’ average score in pre-test was 52,7, and the first post-test was 67,4. The second post-test was 89,8. It means that the post-test was higher than pre-test. Besides, the students also had been well motivated during the learning process. In conclusion, the findings of this research showed that the QL could improve the students’ reading skill. Hence, she suggested to use QL as an alternative method in improving the students’ reading skill.